Translation Analysis of Ideological Aspects through the Use of Rhetorical Constructions in How to Win Friends and Influence People - Nuning Yudhi Prasetyani (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2020)
Rhetorical construction may have a number of functions in a text. It attempts to prompt a reaction to the message of a statement by expressing it in words that have particular connotations. The study aims at the application of rhetorical constructions reflecting the author’s ideology, Dale Carnegie, in ‘How to Win Friends and Influence People’ and how the translator rendered them through the selection of translation techniques into Indonesian version using Van Dijk’s CDA model to determine the quality of translation. By applying a content analysis, the study finds that in general the author uses rhetorical constructions such as repetitions, metaphors, rhetorical questions, and hyperboles to represent his ideology in this book. The author explores a lot on the persuasive and motivational ideology. The findings also show evidence that the translator implements several different translation techniques, such as established equivalent, variation, transposition, amplification, and modulation in order to attain a high quality of translation and to preserve the author’s ideology. Meanwhile, the use of translation techniques such as literal, reduction, generalization, modulation (optional), and discursive creation result in a lower quality of translation and also create a shift (in form and meaning) in the translated version. Thus, these techniques used show the translator’s ability to comprehend what is behind the text, and the translator must also take into consideration any shift in meaning of the ideological construction in the translation process so as to avoid a low quality of translation. This implies that translator should consider the ideology behind the author’s intention to deliver his or her message and chooses the appropriate techniques of translation to maintain the original message in the translated version